2021
DOI: 10.47552/ijam.v12i1.1773
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutico-analytical profile of Mrityunjay Rasa and evaluation of its Antibacterial activity

Abstract: Background: Mrityunjay Rasa is the one of the Kharaliya Kalpana explained in Yogaratnakara in Jwara chikitsa and indicated in all types of fever. Any pathology can leads to diseases which are easily seen by fever as a clinical symptom. Bacterial infections through the skin or by any system defiantly reflect through fever and as told in classics Mrityunjay Rasa is having the capacity to eradicate all types of Jwara. Aim & Objective: The study is planned to evaluate the antibacterial activity of Mrityunjay R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Padikara Parpam had been reported with a ZOI of 14 mm at 4 mg/mL concentration 67 and Mupoora Chendooram was identified with a ZOI of 10 mm at the concentration of 25 mg/mL 22 against S. aureus. Similarly, Mrityunjay Rasa sample showed a ZOI of 20 mm 68 , Thazhampoo Mathirai displayed a ZOI of 16 mm 69 , Kanagalinga Mezhugu presented a ZOI of 15–19 mm 70 . However, all these results showing ZOI against S. aureus strains were comparatively lesser than the potential activity of Sivanar Amirtham .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Padikara Parpam had been reported with a ZOI of 14 mm at 4 mg/mL concentration 67 and Mupoora Chendooram was identified with a ZOI of 10 mm at the concentration of 25 mg/mL 22 against S. aureus. Similarly, Mrityunjay Rasa sample showed a ZOI of 20 mm 68 , Thazhampoo Mathirai displayed a ZOI of 16 mm 69 , Kanagalinga Mezhugu presented a ZOI of 15–19 mm 70 . However, all these results showing ZOI against S. aureus strains were comparatively lesser than the potential activity of Sivanar Amirtham .…”
Section: Discussionmentioning
confidence: 90%
“…The activity of the metallo drugs toward the microorganisms could be linked to the variations in the morphological characteristics between gram-positive and gram-negative microorganisms 75 . Herbomineral formulations like Mrityunjay Rasa and Mahavat Vidhwansan Rasa also showed no activity against P. aeruginosa 68 , 71 . This might be due to the surface charge and the electrostatic attraction between the metal complexes with microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on efficacy of various Ayurvedic formulations were reported. Few of the related studies were reviewed [29][30].…”
Section: Discussionmentioning
confidence: 99%
“…capabilities) and yogavahi (capacity to deliver drugs to specific tissues) properties, it's also non -toxic, gentle to absorb, adaptive, and digestible in the body.The Bhasma of Rasashastra are indeed the tune of modern nanoparticle technology [16][17][18].…”
Section: Discussionmentioning
confidence: 99%